Does female empowerment promote economic development? - Matthias Doepke; Michèle Tertilt (Institute for the Study of Labor (IZA), 2011)
Empirical evidence suggests that money in the hands of mothers (as opposed to their husbands) benefits children. Does this observation imply that targeting transfers to women is good economic policy? We develop a series of noncooperative family bargaining models to understand what kind of frictions can give rise to the observed empirical relationships. We then assess the policy implications of these models. We find that targeting transfers to women can have unintended consequences and may fail to make children better off. Moreover, different forms of empowering women may lead to opposite results. More research is needed to distinguish between alternative theoretical models.
urn:nbn:de:101:1-201104134490
Keywords: D13; J16; O10; 330; female empowerment; gender equality; development; theory of the household; marital bargaining; Frauenpolitik; Entwicklungshilfe; Fraueneinkommen; Entwicklung; Familienökonomik; Haushaltsökonomik; Verhandlungstheorie; Nichtkooperatives Spiel; Ehe; Theorie